The Influence Of Work Discipline And Work Environment On The Performance Of Production Employees At The Kamiya Home Industry Company - Nurmalasari Nurmalasari; Askolani Askolani; Barin Barlian (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
This study aims to determine the simultaneous and partial effect of work discipline and work environment on the performance of production employees at the KAMIYA home industry company. The research method used is descriptive method with a quantitative approach. The sampling technique used a saturated sample with a total sample of 45 people. The data collection technique uses an offline questionnaire. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 25. The results of the study show that work discipline and work environment simultaneously have a significant effect on performance. Partially work discipline has a significant effect on performance. Partially, the work environment has a significant effect on performance.